Evaluasi Program Pembelajaran Metode Ummi dalam Meningkatkan Kemampuan Membaca Al-Qur’an di SMP - Sita Nila Wahyuni; Nurul Aisyah (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The aims of this research is to analyze context, input, process, and product of Tahfidz Al-Qur’an program at SMP Muhammadiyah 1 Gamping. The type of this research is evaluative research with a qualitative approach and use an evaluation model of CIPP (Context, Process, Input, Product)by Stufflebeam. Data collection techniques with observation, interview, and documentation. Analysis of this data using data reduction and conclusion. The results of this study are (1) in the context component, the goals and objectives of Tahfidz Al-qur’an program have been a means category that has a purpose to inculcate the Quranic values and familiarize the atmosphere of the Qur’an in life. (2) in the input, the component shows that the input of teachers, methods, and facilities have been a quite good category, but in teacher input still lack educator to guide tahfidz to be more effective in guiding, while input means to study Tahfidz still less comfortable because there is no place specifically so as not to disturbed student concentration (3) in the process component shows that the implementation schedule is held every day, the target of memorization is 2 juz, but in the achievement of the target, not all student can achieve 2 juz (4) in the product, component shows the results and impact of the Tahfidz program can be categorized well. And the completeness of the achievement of Tahfidz Al-Qur’an program has a value 50 % and categorized “means”.